Pre-lithiated silicon-based negative electrode material, preparation method thereof, negative electrode and lithium ion battery

CN117673291BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211057434.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-31
Publication Date
2026-10-16
Estimated Expiration
2042-08-31

AI Technical Summary

Technical Problem

通过将外源锂以合适的方式和形态引入电池体系,用以改善由于硅负极对有效锂的消耗导致的首次库伦效率降低

Benefits of technology

[0028]Through the above technical solution, this disclosure provides a pre-replenished lithium silicon-based anode material and its preparation method, as well as an anode and a lithium-ion battery. The anode material introduces metallic lithium and lithium oxide into the pores of a porous silicon matrix to form a core structure, achieving the purpose of high lithium content pre-introduction. This effectively avoids the initial reduction in coulombic efficiency of the anode material, increases the battery energy density, replenishes the consumption of effective lithium in the battery, alleviates volume expansion, and improves the coulombic efficiency and cycle stability of the battery. The metallic lithium is confined in the pores of the porous silicon-based material and releases lithium during charge-discharge cycles, replenishing the consumption and loss of lithium ions during battery cycles, which helps to improve cycle stability. Furthermore, the anode material is coated with a carbon coating layer outside the core to prevent the core from directly contacting the outside environment, further improving the coulombic efficiency and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117673291B_ABST
    Figure CN117673291B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a pre-lithiated silicon-based negative electrode material, a preparation method thereof, a negative electrode and a lithium ion battery. The negative electrode material comprises negative electrode material particles with a core-shell structure. The inner core of the negative electrode material particles comprises a porous silicon matrix and lithium elements dispersed on the surface of the silicon matrix and in the pores of the silicon matrix. The lithium elements comprise metallic lithium and / or lithium oxide. The outer shell of the negative electrode material particles comprises a carbon coating layer covering the inner core. The first coulomb efficiency and the cycle stability of the silicon negative electrode material in the lithium ion battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to lithium-ion battery materials, specifically to a pre-compensated lithium-silicon-based anode material and its preparation method, as well as the anode and lithium-ion battery. Background Technology

[0002] The energy density and cycle life of lithium-ion batteries have a significant impact on the use of electronic products. High-energy-density lithium-ion batteries are gradually becoming the main development direction. Improving battery energy density can rely on increasing the capacity of the positive and negative electrode materials. Currently, the commercially available negative electrode material is graphite, with a theoretical specific capacity of 372 mAh g⁻¹. -1 However, these materials are no longer sufficient to meet the demands of high-energy-density batteries. Therefore, developing novel lithium-ion battery anode materials is of great significance in order to meet the energy needs of the next generation and improve battery energy density.

[0003] Silicon materials possess advantages such as high theoretical capacity, abundant reserves, and low discharge voltage. The transition from graphite to silicon-based anode materials can significantly improve the energy density of power batteries. However, silicon materials experience massive volume expansion (>300%) during lithium insertion / extraction, causing the anode material to pulverize and detach, forming "dead silicon," ultimately leading to the loss of electrical contact and battery failure. Furthermore, repeated volume expansion and contraction cause the surface SEI film to continuously break down and form, constantly consuming the Li₂ of the cathode. + This leads to a decrease in battery coulombic efficiency. These problems ultimately cause a sharp deterioration in battery cycle performance, severely impacting battery lifespan.

[0004] Pre-lithiation technology offers an effective solution to address irreversible capacity loss and improve coulombic efficiency. Pre-lithiation technology can be categorized into powder pre-lithiation and electrode pre-lithiation, primarily including lithium-replenishing additives, stabilized lithium metal powder, electrochemical pre-lithiation, contact short-circuit reaction, and chemical pre-lithiation. Currently, most solutions to the low initial efficiency of silicon anodes employ electrode-level pre-lithiation. However, electrode-level pre-lithiation processes require additional pre-lithiation steps, as well as corresponding equipment and environmental space, significantly increasing the time cost, equipment investment cost, and factory renovation cost of lithium battery manufacturing. This hinders the widespread use of silicon anode materials and impedes the development of lithium batteries towards higher energy density and longer lifespan. Furthermore, current pre-lithiation methods face many challenges in practical applications, such as complex processes, stringent preparation conditions, poor compatibility with existing battery systems, and poor operability.

[0005] Pre-lithiation with powder is one of the most direct and effective methods to improve the initial coulombic efficiency of silicon anodes. By introducing exogenous lithium into the battery system in a suitable manner and form, the reduction in initial coulombic efficiency caused by the consumption of effective lithium by the silicon anode can be mitigated. However, it is currently difficult to increase the lithium content of pre-lithiation with powder. When the lithium content is high, the material itself is unstable and difficult to store, and during the slurry preparation process, it is prone to reacting with binders and / or solvent water, making it difficult to form a slurry and thus deteriorating battery performance. Summary of the Invention

[0006] The purpose of this disclosure is to provide a pre-compensated lithium silicon-based anode material and its preparation method, as well as the anode and lithium-ion battery, which can effectively improve the initial coulombic efficiency and cycle stability of silicon anode materials in lithium-ion batteries.

[0007] To achieve the above objectives, the first aspect of this disclosure provides a pre-compensated lithium-silicon-based anode material, the anode material comprising anode material particles having a core-shell structure, wherein the core of the anode material particles comprises a porous silicon matrix and lithium elements dispersed on the surface of the silicon matrix and within the pores of the silicon matrix; the lithium elements comprise metallic lithium and / or lithium oxide; and the outer shell of the anode material particles comprises a carbon coating layer covering the core.

[0008] Optionally, the lithium content in the negative electrode material particles is 5-50% by weight, preferably 10-30% by weight; the carbon coating content in the negative electrode material particles is 5-200% by weight, preferably 20-50% by weight.

[0009] Optionally, the average particle size of the negative electrode material particles is 0.2–20 μm, the average pore size of the negative electrode material particles is 1–50 nm, and the BET specific surface area is 0.5–100 m². 2 / g, total pore volume is 0.01~0.5cm³ 3 / g; Optionally, the thickness of the carbon coating layer of the negative electrode material particles is 1 to 1000 nm.

[0010] A second aspect of this disclosure provides a method for preparing a pre-supplemented lithium silicon-based anode material, the method comprising the following steps:

[0011] S1. Mix lithium metal with porous silicon-based material powder, and then perform solid-phase homogenization treatment to obtain a first mixture; wherein the mass ratio of lithium metal to porous silicon-based material powder is 1:(10-45);

[0012] S2. Add the solid dispersant to the first mixture and perform dispersion and homogenization treatment to obtain the second mixture;

[0013] S3. Add the carbon source to the second mixture and perform carbon coating homogenization treatment to obtain a lithium-silicon-based anode material precursor.

[0014] S4. The lithium-silicon-based anode material precursor is subjected to sintering treatment.

[0015] Steps S1 to S4 are carried out under an inert atmosphere.

[0016] Optionally, in step S1, the porous silicon-based material powder has an average particle size of 0.5–10 μm, an average pore size of 1–50 nm, and a BET specific surface area of ​​0.1–50 m². 2 / g, total pore volume is 0.001~0.5cm³ 3 / g; the lithium metal is selected from one or more of lithium ingots, lithium wires, lithium powders or lithium sheets; preferably, the mass ratio of the lithium metal to the porous silicon-based material powder is 1:(10-30).

[0017] Optionally, before step S1, the method further includes: acid etching the silicon alloy raw material with acid, followed by washing and drying to obtain the porous silicon-based material powder; optionally, the silicon alloy is selected from one or more of silicon-aluminum alloy, silicon-iron alloy, and silicon-magnesium alloy; the silicon content in the silicon alloy raw material is 30-70% by weight.

[0018] Optionally, in step S1, the solid phase homogenization treatment method includes mechanical homogenization, wherein the mechanical homogenization is selected from any one of ball mill, sand mill, homogenizer and disperser; Optionally, in step S1, the rotation speed of the solid phase homogenization treatment is 300-2000 r / min, the homogenization time is 6-72 h, and the ball-to-material ratio is (1-50):1.

[0019] Optionally, in step S2, the solid dispersant is selected from one or more of natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon and soft carbon; the mass ratio of the solid dispersant to the lithium metal is (0.1~1):1, preferably (0.2~0.5):1.

[0020] Optionally, in step S2, the dispersion and homogenization process includes mechanical homogenization, which is selected from any one of ball mill, sand mill, homogenizer and disperser; the rotation speed of the dispersion and homogenization process is 50 to 500 r / min, the time is 0.5 to 12 h, and the ball-to-material ratio is (1 to 50): 1.

[0021] Optionally, in step S3, the carbon source is selected from one or more of polymer carbon sources, petroleum carbon sources, sugar carbon sources, graphite carbon sources, and other carbon sources; the polymer carbon source includes one or more of phenolic resin, epoxy resin, polyvinylpyrrolidone, and polyvinyl alcohol; the petroleum carbon source includes one or more of pitch, petroleum coke, and needle coke; the sugar carbon source includes one or more of glucose, sucrose, and fructose; the graphite carbon source includes one or two of natural graphite and artificial graphite; the other carbon sources include one or more of mesophase carbon microspheres, hard carbon, and soft carbon; the mass ratio of lithium metal to the carbon source is 1:(0.2-20), preferably 1:(1-10).

[0022] Optionally, in step S3, the carbon coating homogenization process includes mechanical homogenization, which is selected from any one of ball mill, sand mill, homogenizer and disperser; the rotation speed of the carbon coating homogenization process is 100-500 r / min, the time is 0.5-12 h, and the ball-to-material ratio is (10-30):1.

[0023] Optionally, in step S4, the sintering process includes a first-stage sintering and a second-stage sintering; wherein the temperature of the first-stage sintering is 200–400°C, the heating rate is 0.5–2°C / min, and the holding time is 1–6 h; the temperature of the second-stage sintering is 400–1200°C, the heating rate is 0.5–5°C / min, and the holding time is 1–12 h; preferably, the temperature of the first-stage sintering is 250–300°C, the heating rate is 1–1.5°C / min, and the holding time is 2–4 h; the temperature of the second-stage sintering is 800–1000°C, the heating rate is 2–3°C / min, and the holding time is 2–5 h.

[0024] Optionally, the inert atmosphere comprises one or more of nitrogen, helium, neon, argon, krypton, and xenon; the water content of the inert atmosphere is less than 0.1% by weight, and the oxygen content is less than 0.1% by weight.

[0025] The third aspect of this disclosure provides a pre-compensated lithium silicon-based anode material prepared using the method described in the second aspect of this disclosure.

[0026] This disclosure provides a fourth aspect of a lithium-ion battery negative electrode, comprising the negative electrode material described in the first or third aspect of this disclosure.

[0027] This disclosure provides a fifth aspect of a lithium-ion battery, including the negative electrode material described in the first or third aspect of this disclosure, or the negative electrode described in the fourth aspect of this disclosure.

[0028] Through the above technical solution, this disclosure provides a pre-replenished lithium silicon-based anode material and its preparation method, as well as an anode and a lithium-ion battery. The anode material introduces metallic lithium and lithium oxide into the pores of a porous silicon matrix to form a core structure, achieving the purpose of high lithium content pre-introduction. This effectively avoids the initial reduction in coulombic efficiency of the anode material, increases the battery energy density, replenishes the consumption of effective lithium in the battery, alleviates volume expansion, and improves the coulombic efficiency and cycle stability of the battery. The metallic lithium is confined in the pores of the porous silicon-based material and releases lithium during charge-discharge cycles, replenishing the consumption and loss of lithium ions during battery cycles, which helps to improve cycle stability. Furthermore, the anode material is coated with a carbon coating layer outside the core to prevent the core from directly contacting the outside environment, further improving the coulombic efficiency and cycle stability of the battery.

[0029] The preparation method disclosed herein is a solid-phase homogeneous reaction method, compatible with existing lithium-ion battery anode material-based assembly systems, and can be directly applied to existing lithium-ion battery anode material systems. It also features high and controllable lithium content, simple process, easy operation, environmentally friendly process, low cost, and suitability for large-scale production.

[0030] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description

[0031] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings:

[0032] Figure 1 This is a schematic diagram of an exemplary structure of pre-filled lithium anode material particles provided in this disclosure;

[0033] Figure 2 A scanning electron microscope image of the pre-lithium-supplemented anode material prepared in Example 1;

[0034] Figure 3 Transmission electron microscope (TEM) image of the pre-lithium-supplemented anode material prepared in Example 1;

[0035] Figure 4 The X-ray diffraction pattern of the pre-lithium-supplemented anode material prepared in Example 1;

[0036] Figure 5 The Li 1s X-ray photoelectron high-resolution scanning energy spectrum of the pre-replenished lithium anode material prepared in Example 1;

[0037] Figure 6 The first charge-discharge curve of the battery assembled using the pre-replenished lithium anode material prepared in Example 1 at a current density of 0.2C;

[0038] Figure 7 The first charge-discharge curves of the battery assembled using porous silicon prepared in Comparative Example 1 at a current density of 0.2C are shown. Detailed Implementation

[0039] The specific embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this disclosure.

[0040] The first aspect of this disclosure provides a pre-compensated lithium-silicon-based anode material, such as... Figure 1 As shown, the anode material includes anode material particles with a core-shell structure. The core of the anode material particles includes a porous silicon matrix and lithium elements dispersed on the surface of the silicon matrix and within the pores of the silicon matrix. The lithium elements include metallic lithium and / or lithium oxide. The outer shell of the anode material particles includes a carbon coating layer covering the core.

[0041] This disclosure provides a pre-replenished lithium-silicon-based anode material. The anode material introduces metallic lithium and lithium oxide into the pores of a porous silicon matrix to form a core structure. This pre-introduction of high lithium content effectively avoids the initial reduction in coulombic efficiency of the anode material, increases battery energy density, replenishes the effective lithium consumption of the battery, alleviates volume expansion, and improves the battery's coulombic efficiency and cycle stability. The metallic lithium is confined within the pores of the porous silicon-based material, releasing lithium during charge-discharge cycles to replenish the consumption and loss of lithium ions during battery cycling, thus contributing to improved cycle stability. Furthermore, the anode material is coated with a carbon layer outside the core, preventing direct contact between the core and the external environment, further improving the battery's coulombic efficiency and cycle stability.

[0042] In one specific embodiment, during the introduction process, lithium metal also reacts with silicon in the porous silicon matrix to form a lithium silicon alloy, wherein the lithium element comprises one or more of lithium metal, lithium oxide, and lithium silicon alloy.

[0043] In one embodiment, the lithium content in the negative electrode material particles is 5-50% by weight; preferably 10-30% by weight. In another embodiment, the carbon coating content in the negative electrode material particles is 5-90% by weight, preferably 20-50% by weight. The negative electrode material particles provided in this disclosure achieve high pre-lithiation, which is beneficial to improving the initial coulombic efficiency and cycle stability of lithium-ion batteries.

[0044] In one embodiment, the average particle size of the negative electrode material particles is 0.2–20 μm, preferably 10–20 μm; the average pore size of the negative electrode material particles is 1–50 nm, preferably 5–20 nm; and the BET specific surface area is 0.5–100 m². 2 / g, preferably 1-5m 2 / g; total pore volume is 0.001~0.5cm³ 3 / g, preferably 0.001~0.1cm 3 / g; the thickness of the carbon coating layer of the negative electrode material particles is 1-1000 nm, preferably 10-100 nm. In this disclosure, the thickness of the carbon coating layer indicates that the thickness of the carbon coating layer of the negative electrode material particles is within this range. For example, "the thickness of the carbon coating layer is 1-1000 nm" means that the thickness of the carbon coating layer at any position of the negative electrode material particles is within the range of 1-1000 nm. In this disclosure, the thickness of the carbon coating layer can be obtained by transmission electron microscopy (TEM) images.

[0045] A second aspect of this disclosure provides a method for preparing a pre-supplemented lithium silicon-based anode material, the method comprising the following steps:

[0046] S1. Mix lithium metal with porous silicon-based material powder, and then perform solid-phase homogenization treatment to obtain a first mixture; wherein the mass ratio of lithium metal to porous silicon-based material powder is 1:(10-45);

[0047] S2. Add the solid dispersant to the first mixture and perform dispersion and homogenization treatment to obtain the second mixture;

[0048] S3. Add the carbon source to the second mixture and perform carbon coating homogenization treatment to obtain a lithium-silicon-based anode material precursor.

[0049] S4. The lithium-silicon-based anode material precursor is subjected to sintering treatment.

[0050] Steps S1 to S4 are carried out under an inert atmosphere.

[0051] The preparation method disclosed herein is a solid-phase homogeneous reaction method, compatible with existing lithium-ion battery anode material-based assembly systems, and can be directly applied to existing lithium-ion battery anode material systems. It also features high and controllable lithium content, simple process, easy operation, environmentally friendly process, low cost, and suitability for large-scale production.

[0052] Specifically, in the solid-phase homogenization process of step S1, this disclosure adds a high content of metallic lithium. The metallic lithium is sufficient to react with the oxygen on the porous silicon-based material powder to generate lithium oxide, which can solve the problem of the initial coulombic efficiency reduction of silicon itself. At the same time, it acts as a buffer medium to buffer the volume expansion during the cycle, making the material structure more stable. In addition, a portion of metallic lithium does not participate in the reaction and is confined in the pores of the porous silicon-based material in the form of metallic lithium. During the charge-discharge cycle, lithium is released to replenish the consumption and loss of lithium ions during the battery cycle and improve the cycle stability.

[0053] In a preferred embodiment, the mass ratio of lithium metal to the porous silicon-based material powder is 1:(10-30). By optimizing the mass ratio of lithium metal to the porous silicon-based material powder, lithium can be further introduced, thereby further improving the initial coulombic efficiency and cycle performance of the lithium-ion battery.

[0054] In one specific embodiment, in steps S1 to S4, the inert atmosphere includes one or more of nitrogen, helium, neon, argon, krypton, and xenon; the water content of the inert atmosphere is less than 0.1% by weight, and the oxygen content is less than 0.1% by weight.

[0055] In one embodiment, in step S1, the porous silicon-based material powder has an average particle size of 0.5–10 μm, an average pore size of 1–50 nm, and a BET specific surface area of ​​0.1–50 m². 2 / g, total pore volume is 0.001~0.5cm³ 3 / g; In a preferred embodiment, the porous silicon-based material powder has an average particle size of 2-5 μm, an average pore size of 5-20 nm, and a BET specific surface area of ​​0.1-10 m². 2 / g, total pore volume is 0.001~0.1cm³ 3 / g;

[0056] The lithium metal is selected from one or more of lithium ingots, lithium wires, lithium powder, or lithium sheets.

[0057] According to this disclosure, porous silicon-based material powders can be obtained through conventional purchasing channels or prepared using methods known in the art.

[0058] In one specific embodiment, before step S1, the method further includes:

[0059] The silicon alloy raw material is subjected to acid etching treatment, followed by washing and drying to obtain the porous silicon-based material powder.

[0060] Optionally, the silicon alloy is selected from one or more of silicon-aluminum alloy, silicon-iron alloy, and silicon-magnesium alloy; the silicon content in the silicon alloy raw material is 30-70% by weight.

[0061] In one embodiment, the acid is selected from one or more of hydrochloric acid, sulfuric acid, and nitric acid; the concentration of the acid is 0.1–2 mol / L; and the acid etching conditions include a time of 4–36 hours. This disclosure, by modifying inexpensive silicon alloy materials and introducing a porous structure within the material, offers advantages such as low cost and ease of large-scale production, which can promote the practical application of silicon-based anode materials.

[0062] In one specific embodiment, in step S1, the solid phase homogenization process includes mechanical homogenization, wherein the mechanical homogenization is selected from any one of ball mill, sand mill, homogenizer and disperser.

[0063] In one embodiment, in step S1, the rotation speed of the solid-phase homogenization process is 300–2000 r / min, the homogenization time is 6–72 h, and the ball-to-material ratio is (1–50):1. This disclosure employs a solid-phase homogenization reaction process, which allows the oxygen on the silicon material surface to react with metallic lithium as fully as possible. It is simple, easy to implement, and suitable for large-scale production.

[0064] In a preferred embodiment, in step S1, the rotation speed of the solid-phase homogenization process is 500–1000 r / min, the homogenization time is 12–24 h, the homogenization temperature is 80–150 °C, and the ball-to-material ratio is (10–30):1. The preferred reaction parameters of this embodiment are beneficial for improving the solid-phase homogenization reaction effect.

[0065] In one embodiment, in step S2, the solid dispersant is selected from one or more of natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, and soft carbon. The introduction of graphite-based solid dispersants in this disclosure can prevent silicon and lithium from agglomerating during the ball milling reaction, ensuring sufficient dispersion of silicon-lithium particles; simultaneously, the dispersant can also form a diffusely distributed conductive network, increasing particle conductivity and suppressing the decrease in conductivity caused by the introduction of lithium.

[0066] In a preferred embodiment, the mass ratio of the solid dispersant to the lithium metal is (0.1-1):1, more preferably (0.2-0.5):1.

[0067] In one specific embodiment, in step S2, the dispersion and homogenization process includes mechanical homogenization, wherein the mechanical homogenization is selected from any one of ball mill, sand mill, homogenizer and disperser.

[0068] In one embodiment, in step S2, the dispersion and homogenization process is carried out at a rotation speed of 50–500 r / min for 0.5–12 h, and the ball-to-material ratio is (10–50):1. In a preferred embodiment, in step S2, the dispersion and homogenization process is carried out at a rotation speed of 100–450 r / min for 0.5–5 h, and the ball-to-material ratio is (10–30):1.

[0069] In one embodiment, in step S3, the carbon source is selected from one or more of polymer carbon sources, petroleum-based carbon sources, sugar-based carbon sources, graphite-based carbon sources, and other carbon sources;

[0070] The polymer carbon source includes one or more of phenolic resin, epoxy resin, polyvinylpyrrolidone, and polyvinyl alcohol;

[0071] The petroleum-based carbon sources include one or more of pitch, petroleum coke and needle coke;

[0072] The carbohydrate carbon source includes one or more of glucose, sucrose, and fructose;

[0073] The graphite-based carbon source includes one or both of natural graphite and artificial graphite;

[0074] The other carbon sources include one or more of mesophase carbon microspheres, hard carbon, and soft carbon.

[0075] Typically, after pre-lithiation of the negative electrode material, the alkalinity of the material increases due to the introduction of lithium. During the preparation of the negative electrode slurry, the molecular chains of the binder are broken, leading to a lower viscosity of the slurry, or even reaction with the binder and / or solvent water, making slurry preparation difficult. This disclosure introduces a carbon source for coating during this process, forming a carbon coating layer on the surface of the silicon-lithium particles. This prevents the particles from reacting with the binder and / or solvent water during slurry preparation. Simultaneously, the carbon coating layer protects the internal lithium from oxidation and failure during environmental transfer. Furthermore, the carbon coating layer further suppresses the decrease in conductivity caused by lithium insertion, thereby improving the initial coulombic efficiency and cycle stability of the battery made from this material.

[0076] In one embodiment, the mass ratio of the carbon source to the lithium metal is (0.2-20):1, preferably (1-10):1.

[0077] In one specific embodiment, in step S3, the carbon coating homogenization process includes mechanical homogenization, wherein the mechanical homogenization is selected from any one of ball mill, sand mill, homogenizer and disperser.

[0078] In one embodiment, the carbon coating homogenization process is carried out at a rotation speed of 100–500 r / min for 0.5–12 h, with a ball-to-material ratio of (10–30):1. In a preferred embodiment, the carbon coating homogenization process is carried out at a rotation speed of 300–450 r / min for 2–5 h, with a ball-to-material ratio of (10–20):1.

[0079] In one embodiment, step S4, the sintering process includes a first-stage sintering and a second-stage sintering. The temperature of the first-stage sintering is 200–400°C, the heating rate is 0.5–2°C / min, and the holding time is 1–6 h. The temperature of the second-stage sintering is 400–1200°C, the heating rate is 0.5–5°C / min, and the holding time is 1–12 h. This disclosure achieves thermal stabilization through segmented heating sintering and limits the thermal stabilization temperature within the above-mentioned range, which can suppress the growth of silicon grains inside the silicon particles and further prevent a decrease in cycle stability.

[0080] In a preferred embodiment, the sintering temperature of the first stage is 250–300°C, the heating rate is 1.0–1.5°C / min, and the holding time is 2–4 h; the sintering temperature of the second stage is 800–1000°C, the heating rate is 2–3°C / min, and the holding time is 2–5 h. The preferred sintering parameters in this embodiment can further improve the cycle stability of the negative electrode material.

[0081] The third aspect of this disclosure provides a pre-compensated lithium silicon-based anode material prepared using the method described in the second aspect of this disclosure.

[0082] This disclosure provides a fourth aspect of a lithium-ion battery anode, comprising the lithium-containing silicon-based anode material described in the first or third aspect of this disclosure.

[0083] According to this disclosure, the negative electrode of the lithium-ion battery can be prepared using methods known in the art. For example, the negative electrode is obtained by coating a slurry, the slurry including the negative electrode material, conductive agent, binder, etc. provided in this disclosure, wherein the conductive agent and binder are conventionally selected in the art.

[0084] This disclosure provides a fifth aspect of a lithium-ion battery, which includes the lithium-containing silicon-based anode material described in the first or third aspect of this disclosure, or the anode described in the fourth aspect of this disclosure.

[0085] According to this disclosure, lithium-ion batteries can be assembled using methods known in the art.

[0086] The high-compensation lithium-silicon-based anode material disclosed herein can be directly applied to existing lithium-ion battery anode systems, and can also be used in combination with lithium-ion battery graphite anode materials, silicon-carbon anode materials, and silicon suboxide anode materials. When this high-compensation lithium-silicon-based anode material is applied to lithium-ion batteries, it significantly improves the initial coulombic efficiency and cycle stability of the lithium-ion battery.

[0087] The present disclosure will be further illustrated by the following examples, but the present disclosure is not limited thereto.

[0088] Unless otherwise specified, all raw materials used in the following embodiments are commercially available products.

[0089] In the following embodiments, the specific testing methods are as follows:

[0090] The average particle size was tested using a particle size analyzer, specifically a Mastersizer 3000 instrument.

[0091] The test methods for BET specific surface area, average pore size and pore volume include: using a specific surface area and pore size analyzer JW-BK100;

[0092] The testing method for scanning electron microscopy (SEM) was a scanning electron microscope, and the instrument model was Hitachi S4800 from Japan.

[0093] The testing method for transmission electron microscopy (TEM) was a transmission electron microscope, and the instrument model was a Hitachi H-800 transmission electron microscope from Japan.

[0094] The XRD test method was an X-ray diffractometer, specifically the PANalytical X'Pert PRO powder X-ray diffractometer.

[0095] The XPS test method is X-ray photoelectron spectroscopy, and the instrument model is VG ESCALAB;

[0096] The electrochemical cycling performance was tested using the Blue Electric Test System, instrument model CT3001A.

[0097] Preparation Example 1

[0098] This preparation example illustrates the preparation of porous silicon material powder, specifically including: etching an aluminum alloy with a silicon content of 60 wt% using excess hydrochloric acid at a concentration of 1 mol / L. -1 The reaction time was 10 hours. After the reaction was complete, the mixture was washed with deionized water until neutral and dried in a vacuum oven at 60°C for 12 hours to obtain porous silicon, denoted as DKG-1.

[0099] Testing revealed that the DKG-1 product has an average particle size of 3.5 μm, an average pore size of 7.78 nm, and a BET specific surface area of ​​1.83 m². 2 / g, total pore volume is 0.004cm³ 3 / g.

[0100] Preparation Example 2

[0101] This preparation example illustrates the preparation of porous silicon material powder, specifically including: etching a silicon-aluminum alloy with a silicon content of 70 wt% using excess sulfuric acid with a sulfuric acid concentration of 1 mol / L. -1 The reaction time was 24 hours. After the reaction was complete, the mixture was washed with deionized water until neutral and dried in a vacuum oven at 60°C for 12 hours to obtain porous silicon, denoted as DKG-2.

[0102] Testing revealed that the DKG-2 product has an average particle size of 4.6 μm, an average pore size of 7.596 nm, and a BET specific surface area of ​​0.622 m². 2 / g, total pore volume is 0.011cm³ 3 / g.

[0103] Example 1

[0104] Under an anhydrous and oxygen-free inert environment, 2g of the prepared DKG-1 porous silicon and 0.2g of lithium metal ingot were weighed and placed in a zirconia ball mill jar (lithium metal to porous silicon mass ratio of 1:10). After sealing, the jar was transferred to a planetary ball mill for ball milling. The ball-to-material ratio was 20:1, and the zirconia balls had diameters of 5.5mm, 3.0mm, and 2.0mm in a ratio of 2:5:3. The ball milling speed was 500 rpm, and the milling time was 12 hours. Then, 0.1g of natural graphite was added and ball milling continued (lithium to solid dispersant mass ratio of 1:0.5) at a speed of 450 rpm for 2 hours. Finally, 1g of pitch powder was added and ball milling continued (lithium to carbon source mass ratio of 1:5) at a speed of 350 rpm for 2 hours. The resulting material was a silicon-based composite material precursor. The lithium-silicon-based composite precursor was placed in a tube furnace under an argon atmosphere for thermal stabilization sintering. The calcination process involved first heating to 400℃ at a rate of 2℃ / min and holding at that temperature for 1 hour for preheating and stabilization; then heating to 800℃ at a rate of 3℃ / min and holding at that temperature for 2 hours. After cooling to room temperature, the pre-compensated lithium-silicon-based anode material, denoted as YBL-1, was obtained.

[0105] Figure 2 This is a SEM image of YBL-1, the lithium-added silicon-based anode material prepared in Example 1. Figure 2 As can be seen, the lithium-added silicon-based anode material is granular with a relatively smooth surface structure, and the particle surface is coated with a film.

[0106] Figure 3 This is a TEM image of YBL-1, the lithium-supplemented silicon-based anode material prepared in Example 1. Figure 3 As can be seen, the material edges have a layered structure, denoted as the outer carbon coating layer; from Figure 3 It can also be seen that the lithium-based silicon anode material has a lot of pits and pores inside (the darker areas in the dashed boxes in the figure), which can provide a confined and protective space for the introduction of lithium.

[0107] Figure 4 The X-ray diffraction pattern of YBL-1, the lithium-supplemented silicon-based anode material prepared in Example 1, is shown in the pattern. The pattern reveals that the product mainly consists of silicon and carbon, with obvious diffraction peaks for lithium (metallic lithium and / or lithium oxide) appearing (the diffraction peaks of metallic lithium and lithium oxide are superimposed), indicating that lithium was successfully introduced into the porous silicon.

[0108] Figure 5The figure shows the Li 1s X-ray photoelectron high-resolution scanning energy spectrum of YBL-1, a lithium-supplemented silicon-based anode material prepared in Example 1. As can be seen from the figure, there are characteristic peaks of Li on the surface of the product, but the intensity is weak, indicating that lithium was successfully introduced into the porous silicon. Due to the confinement of the pores and the dual protection of the carbon coating film, the lithium content on the surface of the material is very low.

[0109] Comparative Example 1

[0110] Under an anhydrous and oxygen-free inert environment, 2g of the prepared DKG-1 porous silicon was weighed and placed in a zirconia ball mill jar. After sealing, it was transferred to a planetary ball mill for ball milling. The ball-to-material ratio was 20:1, and the zirconia balls had diameters of 5.5mm, 3.0mm, and 2.0mm in a ratio of 2:5:3. The ball milling speed was 500 rpm, and the milling time was 12 hours. Then, 0.1g of natural graphite was added, and ball milling continued at 450 rpm for 2 hours. The powder was then collected to obtain lithium-free porous silicon, denoted as D-1.

[0111] Comparative Example 2

[0112] Using a similar preparation method and process conditions as in Example 1, the only difference from Example 1 is that natural graphite (solid dispersant) and pitch powder (carbon source) are not added. The rest of the process is the same as in Example 1. A lithium-containing silicon-carbon composite material, denoted as D-2, was prepared.

[0113] Example 2

[0114] In an anhydrous and oxygen-free inert environment, 2g of the prepared DKG-1 porous silicon and 0.2g of lithium metal sheets were weighed and placed in a zirconia ball mill jar (the mass ratio of lithium metal to porous silicon was 1:10). After sealing, the jar was transferred to a nanoball mill for ball milling. The ball-to-material ratio was 20:1, and the zirconia balls had diameters of 5.5mm, 3.0mm, and 2.0mm in a ratio of 2:5:3. The milling speed was 700 rpm, and the milling time was 24 hours. Then, 0.2g of artificial graphite was added and ball milling continued (the mass ratio of lithium to solid dispersant was 1:1) at a milling speed of 300 rpm for 1 hour. Finally, 1g of pitch powder was added and ball milling continued (the mass ratio of lithium to carbon source was 1:5) at a milling speed of 350 rpm for 2 hours. The resulting material was a silicon-based composite material precursor. The lithium-silicon-based composite precursor was placed in a tube furnace under an argon atmosphere for thermal stabilization sintering. The calcination process involved first heating to 300°C at a rate of 2°C / min, holding at that temperature for 2 hours for preheating and stabilization, then heating to 900°C at a rate of 3°C / min, and then holding at that temperature for 2 hours. After cooling to room temperature, the pre-compensated lithium-silicon-based anode material, denoted as YBL-2, was obtained.

[0115] Example 3

[0116] Under an anhydrous and oxygen-free inert environment, 2g of the prepared DKG-2 porous silicon and 0.1g of lithium metal wire were weighed and placed in a zirconia ball mill jar (the mass ratio of lithium metal to porous silicon was 1:20). After sealing, the jar was transferred to a nanoball mill for ball milling. The ball-to-material ratio was 20:1, and the diameters of the zirconia balls were 5.5mm, 3.0mm, and 2.0mm, with a ratio of 2:5:3. The ball milling speed was 900 rpm, and the milling time was 48 hours. Then, 0.02g of artificial graphite was added and ball milling continued (the mass ratio of lithium to solid dispersant was 1:0.2), with the ball milling speed at 450 rpm and the milling time at 1 hour. Then, 1g of asphalt powder was added and ball milling continued (the mass ratio of lithium to carbon source was 1:10), with the ball milling speed at 350 rpm and the milling time at 2 hours. The silicon-based composite material precursor was then obtained. The lithium-containing silicon-based composite precursor was placed in a tube furnace under an argon atmosphere for thermal stabilization sintering. The calcination process involved first heating to 350°C at a rate of 2°C / min, holding at that temperature for 1 hour for preheating and stabilization, then heating to 700°C at a rate of 3°C / min, and then holding at that temperature for 2 hours. After cooling to room temperature, the lithium-added silicon-based anode material, denoted as YBL-3, was obtained.

[0117] Example 4

[0118] The same preparation method and process conditions as in Example 1 were used, except that in the thermal stabilization sintering process, the calcination process involved first heating to 300°C at a rate of 1.5°C / min and holding at that temperature for 3 hours for preheating and stabilization; then heating to 900°C at a rate of 3°C / min and holding at that temperature for 4 hours. After cooling to room temperature, the lithium-added silicon-based anode material, denoted as YBL-4, was obtained.

[0119] Example 5

[0120] The preparation method and process conditions are similar to those in Example 1, with the only difference being:

[0121] A one-step sintering method was used for thermal stabilization treatment. The lithium-silicon-based composite material precursor was placed in a tube furnace under an argon atmosphere for thermal stabilization sintering. The calcination process involved heating to 800℃ at a rate of 2℃ / min and holding at that temperature for 2 hours. After cooling to room temperature, the lithium-silicon-based anode material, denoted as YBL-5, was obtained.

[0122] Example 6

[0123] The preparation method and process conditions are similar to those in Example 1, with the only difference being:

[0124] Weigh out 4.5g of DKG-1 porous silicon and 0.1g of lithium metal ingot (lithium to porous silicon mass ratio is 1:45);

[0125] Add 0.1g of natural graphite and continue ball milling (lithium to solid dispersant mass ratio is 1:1);

[0126] Add 2g of pitch powder and continue ball milling (the mass ratio of lithium to carbon source is 1:20);

[0127] A lithium-containing silicon-based anode material was obtained, denoted as YBL-6.

[0128] The component content, structural parameters, and other data of the products obtained from the above embodiments and comparative examples are listed in Table 1 below.

[0129] Table 1

[0130]

[0131] Test case

[0132] This test example illustrates the electrochemical performance of the products obtained in the examples and comparative examples when used as negative electrodes in lithium-ion batteries.

[0133] The products obtained in the examples and comparative examples were used as negative electrodes to assemble batteries, and their electrochemical performance was tested. The specific steps are as follows:

[0134] (1) Slurry preparation: Weigh the negative electrode material, conductive agent (carbon black, Tianjin Damao Chemical) and binder (sodium carboxymethyl cellulose, Tianjin Damao Chemical) in a ratio of 8:1:1, add solvent water to adjust the viscosity of the slurry, and stir for 3-5 hours.

[0135] (2) Coating: The slurry is coated onto the copper foil current collector using a doctor blade mold, with a thickness of 120μm.

[0136] (3) Drying: Dry in a vacuum drying oven at 120°C for 12 hours.

[0137] (4) Cutting: Cut into circular negative electrode sheets with a diameter of 15mm, weigh them and place them in a drying oven.

[0138] (5) Assembly: In the glove box, CR2025 button cells are assembled using lithium sheets as the counter electrode.

[0139] The electrolyte was a 1M LiPF6 / EC:DMC (1:1, vol) mixture, and the diaphragm was a Celgard 2300 polypropylene microporous membrane.

[0140] The sealed battery was left to stand for 24 hours, and then charge-discharge and cycle performance tests were conducted using the Land battery performance testing system at a current density of 0.2C. The test results are shown in Table 2.

[0141] Table 2

[0142]

[0143] in, Figure 6 The electrochemical capacity-voltage test results of the lithium-ion battery assembled using the negative electrode material YBL-1 provided in Example 1 show that it has a high specific capacity and initial coulombic efficiency. Figure 7 The results show the electrochemical cycle performance of the battery assembled using lithium-free porous silicon D-1 as the negative electrode material in Comparative Example 1.

[0144] Comparing YBL-1 and D-1, it can be seen that the lithium-supplemented silicon-based anode material prepared using the anode material provided in this disclosure can significantly improve the energy density, initial coulombic efficiency and cycle stability of the battery.

[0145] A comparison of YBL-1 and D-2 shows that the core-shell structured anode material prepared by the method provided in this disclosure has higher initial charge specific capacity, initial coulombic efficiency, and cycle stability.

[0146] Comparing Example 1 and Example 5, it can be seen that Example 1 involves first-stage sintering and second-stage sintering, while Example 5 only uses a one-step sintering method. The pre-compensated lithium silicon-based anode material obtained in Example 1 can achieve higher first-charge specific capacity, first-coulombic efficiency, and cycle stability.

[0147] Comparing Example 1 with Example 6, it can be seen that in Example 1, the mass ratio of lithium metal to porous silicon-based material powder is 1:(10-30), the mass ratio of solid dispersant to lithium metal is (0.2-0.5):1, and the mass ratio of lithium metal to carbon source is 1:(1-10). Using the pre-replenished lithium silicon-based anode material obtained in Example 1 can achieve higher initial charge specific capacity, initial coulombic efficiency, and cycle stability.

[0148] Comparing Example 1 and Example 4, it can be seen that Example 4 satisfies the following conditions during the preparation process: "the temperature of the first stage sintering is 250-300℃, the heating rate is 1-1.5℃ / min, and the holding time is 2-4h; the temperature of the second stage sintering is 800-1000℃, the heating rate is 2-3℃ / min, and the holding time is 2-5h." Using the pre-compensated lithium silicon-based anode material obtained in Example 4 can achieve higher initial charge specific capacity, initial coulombic efficiency, and cycle stability.

[0149] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.

[0150] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.

[0151] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.

Claims

1. A method for preparing pre-compensated lithium silicon-based anode materials, characterized in that, The method includes the following steps: S1. Mix lithium metal with porous silicon-based material powder, and then perform solid-phase homogenization treatment to obtain a first mixture; wherein the mass ratio of lithium metal to porous silicon-based material powder is 1:(10~45). S2. Add the solid dispersant to the first mixture and perform dispersion and homogenization treatment to obtain the second mixture; S3. Add the carbon source to the second mixture and perform carbon coating homogenization treatment to obtain a lithium-silicon-based anode material precursor. S4. The lithium-silicon-based anode material precursor is sintered to obtain a pre-compensated lithium-silicon-based anode material. Steps S1 to S4 are performed under an inert atmosphere. The sintering process includes a first-stage sintering and a second-stage sintering; The first sintering temperature is 200~400℃, the heating rate is 0.5~2℃ / min, and the holding time is 1~6h; the second sintering temperature is 700~1200℃, the heating rate is 2~3℃ / min, and the holding time is 2~5h. The pre-replenished lithium silicon-based anode material includes anode material particles with a core-shell structure; the core of the anode material particles includes a porous silicon matrix and lithium elements dispersed on the surface of the silicon matrix and within the pores of the silicon matrix.

2. The method according to claim 1, characterized in that, In step S1, the porous silicon-based material powder has an average particle size of 0.5~10μm, an average pore size of 1~50nm, and a BET specific surface area of ​​0.1~50m². 2 / g, total pore volume is 0.001~0.5cm³ 3 / g; The lithium metal is selected from one or more of lithium ingots, lithium wires, lithium powder, or lithium sheets.

3. The method according to claim 1, characterized in that, The mass ratio of the lithium metal to the porous silicon-based material powder is 1:(10~30).

4. The method according to claim 1, characterized in that, Before step S1, the method further includes: The silicon alloy raw material is acid-etched, then washed and dried to obtain the porous silicon-based material powder.

5. The method according to claim 4, characterized in that, The silicon alloy is selected from one or more of silicon-aluminum alloy, silicon-iron alloy and silicon-magnesium alloy; the silicon content in the silicon alloy raw material is 30-70% by weight.

6. The method according to claim 1, characterized in that, In step S1, the solid phase homogenization process includes mechanical homogenization, which is selected from any one of ball mill, sand mill, homogenizer and disperser.

7. The method according to claim 1, characterized in that, In step S1, the rotation speed of the solid phase homogenization process is 300~2000 r / min, the homogenization time is 6~72 h, and the ball-to-material ratio is (1~50):

1.

8. The method according to claim 1, characterized in that, In step S2, the solid dispersant is selected from one or more of natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, and soft carbon; The mass ratio of the solid dispersant to the lithium metal is (0.1~1):

1.

9. The method according to claim 8, characterized in that, The mass ratio of the solid dispersant to the lithium metal is (0.2~0.5):

1.

10. The method according to claim 1, characterized in that, In step S2, the dispersion and homogenization process includes mechanical homogenization, which is selected from any one of ball mill, sand mill, homogenizer and disperser; The dispersion and homogenization process is carried out at a rotation speed of 50~500 r / min for 0.5~12 h, with a ball-to-material ratio of (1~50):

1.

11. The method according to claim 1, characterized in that, In step S3, the carbon source is selected from one or more of polymer carbon sources, petroleum-based carbon sources, sugar-based carbon sources, graphite-based carbon sources, and other carbon sources; The polymer carbon source includes one or more of phenolic resin, epoxy resin, polyvinylpyrrolidone, and polyvinyl alcohol; The petroleum-based carbon sources include one or more of pitch, petroleum coke and needle coke; The carbohydrate carbon source includes one or more of glucose, sucrose, and fructose; The graphite-based carbon source includes one or both of natural graphite and artificial graphite; The other carbon sources include one or more of mesophase carbon microspheres, hard carbon, and soft carbon; The mass ratio of the lithium metal to the carbon source is 1:(0.2~20).

12. The method according to claim 11, characterized in that, The mass ratio of the lithium metal to the carbon source is 1:(1~10).

13. The method according to claim 1, characterized in that, In step S3, the carbon coating homogenization process includes mechanical homogenization, which is selected from any one of ball mill, sand mill, homogenizer and disperser; The carbon coating homogenization process is carried out at a rotation speed of 100~500 r / min for 0.5~12 h, with a ball-to-material ratio of (10~30):

1.

14. The method according to claim 1, characterized in that, In step S4, the sintering temperature of the first stage is 250~300℃, the heating rate is 1~1.5℃ / min, and the holding time is 2~4h; The sintering temperature of the second stage is 800~1000℃.

15. The method according to claim 1, characterized in that, The inert atmosphere comprises one or more of nitrogen, helium, neon, argon, krypton, and xenon; the water content and oxygen content of the inert atmosphere are less than 0.1% by weight and less than 0.1% by weight.

16. A pre-compensated lithium silicon-based anode material prepared by the method according to any one of claims 1 to 15.

17. The pre-compensated lithium-silicon-based anode material according to claim 16, characterized in that, The lithium element comprises metallic lithium and / or lithium oxide; the outer shell of the negative electrode material particles includes a carbon coating layer covering the core.

18. The pre-compensated lithium-silicon-based anode material according to claim 16, characterized in that, The negative electrode material has an average particle size of 2.38-10.25 μm, an average pore size of 17.128-28.142 nm, and a BET specific surface area of ​​1.851-4.123 m². 2 / g, total pore volume is 0.010~0.027cm³ 3 / g.

19. The pre-compensated lithium-silicon-based anode material according to claim 16, characterized in that, The thickness of the carbon coating layer of the negative electrode material particles is 5~50nm.

20. A negative electrode for a lithium-ion battery, characterized in that, Includes the negative electrode material as described in any one of claims 16 to 19.

21. A lithium-ion battery, characterized in that, Includes the negative electrode as described in claim 20.

Citation Information

Patent Citations

  • Space buffer lithium-doped silicon oxide composite material, preparation method of composite material and lithium ion battery

    CN108232145A

  • Preparation method of pre-lithium alloy with porous structure

    CN110224122A